A Practical Guide to Teacher Education Evaluation
XVI, 270 p.
Keywords: J. T. Sandefur Western Kentucky University American's ability to compete in world markets is eroding. The productivity growth of our competitors outdistances our own. The capacity of our economy to provide a high standard of living for all our people is increasingly in doubt. As jobs requiring little skill are automated or go offshore and demand increases for the highly skilled, the pool of educated and skilled people grows smaller and the backwater of the unemployable rises. Large numbers of American children are in limbo--ignorant of the past and unprepared for the future. Many are dropping out--notjust out of school--but out of productive society. These are not my words. They are a direct quote from the Executive Summary of the Carnegie Forum Report on Education and the Economy entitled A Nation Prepared: Teachers for the 21st Century (p. 2, 1986). This report was motivated by four purposes: 1. To remind Americans, yet again, of the economic challenges pressing us on all sides; 2. To assert the primacy of education as the foundation of economic growth, equal opportunity and a shared national vision; 3. To reaffirm that the teaching profession is the best hope for establishing new standards of excellence as the hallmark of American education; and 4. To point out that a remarkable window of opportunity lies before us in the next decade to reform education, an opportunity that may not present itself again until well into the next century.